2018
DOI: 10.1038/s41467-018-04197-6
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Nitrogen-rich organic soils under warm well-drained conditions are global nitrous oxide emission hotspots

Abstract: The original version of this Article contained an error in the first sentence of the Acknowledgements section, which incorrectly referred to the Estonian Research Council grant identifier as “PUTJD618”. The correct version replaces the grant identifier with “PUTJD619”. This has been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The explanation power of our statistical models for N 2 O concentrations in lakes (Table 3) is comparable to the power of the models developed for terrestrial N 2 O emissions (Leppelt et al, 2014;Pärn et al, 2018) (Soued et al, 2015).…”
Section: Ta B L Esupporting
confidence: 80%
See 1 more Smart Citation
“…The explanation power of our statistical models for N 2 O concentrations in lakes (Table 3) is comparable to the power of the models developed for terrestrial N 2 O emissions (Leppelt et al, 2014;Pärn et al, 2018) (Soued et al, 2015).…”
Section: Ta B L Esupporting
confidence: 80%
“…The explanation power of our statistical models for N 2 O concentrations in lakes (Table 3) is comparable to the power of the models developed for terrestrial N 2 O emissions (Leppelt et al, 2014;Pärn et al, 2018). In the lake dataset from boreal southern Norway and Sweden, N 2 O concentrations correlated positively with nitrate in summer (Yang et al, 2015).…”
Section: Seasonal and Spatial Variation In N 2 O Concentrations Andsupporting
confidence: 69%
“…the Yangtze River Basin, attributed to the presence of tropical or subtropical intensive agriculture and river systems8,9 ; Parn et al have suggested that prioritizing the management of N 2 O emissions is essential in tropical wetlands 5. There still remains an inevitable limitation in the well-established multiple-regression models, even with significant enhancements made to national models and data sets in this work.…”
mentioning
confidence: 89%
“…4 As a result, nitrous oxide (N 2 O) can be substantially generated through both microbial nitrification either via hydroxylamine oxidation, or hybrid formation, and incomplete denitrification. 5 In situations when oxygen is limiting or completely absent, N 2 O can be further reduced to N gas in the last stage of denitrification. 5,6 A recent study reported that wetlands emitted N 2 O of 0.97 ± 0.70 Tg yr −1 globally were considered as an unignorable N 2 O source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation